"Rights of nature" in translation: Assemblage geographies, boundary objects, and translocal social movements. Issue 3 (1st April 2019) - Kinkaid, Eden
Abstract : In the last 15 years, "rights of nature" as a concept and legal apparatus has spread across various sites and scales of environmental governance throughout the world. This paper examines the rights of nature phenomenon, focusing on a recent decision by the High Court of Uttarakhand, India to grant legal personhood to the Ganga (Ganges) and Yamuna rivers and associated natural entities. Arguing against "diffusionist" and "global" approaches to understanding the rights of nature phenomenon, and drawing on the concept of translocal assemblages, I emphasise the place‐based specificities of these decisions in addition to their translocal connections. Through a close reading of the Uttarakhand case, I demonstrate the need to situate translocal social movements in place by attending to the manner in which "rights of nature" becomes articulated through specific practices, cultural meanings, material networks, human–environment relations, legal regimes, governance structures, and political projects in culturally and geographically specific ways with often counterintuitive outcomes. Rather than seeing "rights of nature" as a global movement or network manifesting at various scales, I consider it as a boundary object connecting translocal assemblages of environmental governance through acts of translation. In doing so, I push assemblage geographies to engage theoretical problems of difference, boundaries, and translation that have yet to be addressed in this emerging paradigm. Abstract : In the last 15 years, "rights of nature" as a concept and legal apparatus has spread across various sites and scales of environmental governance throughout the world. This paper examines the rights of nature phenomenon, focusing on a recent decision by the High Court of Uttarakhand, India to grant legal personhood to the Ganga (Ganges) and Yamuna rivers. Arguing against "diffusionist" and "global" approaches to understanding the rights of nature phenomenon, I consider it as a boundary object connecting translocal assemblages of environmental governance through acts of translation.